Bifunctional Nanoprobes Used for Label‐Free Determination of Cardiac Troponin I. Issue 21 (2nd November 2020) - Xue, Yuan; Han, Yanchao; Xia, Hongyin; Fan, Yongchao; Peng, Chao; Xing, Huanhuan; Li, Jing; Wang, Erkang
Abstract: In this work, bifunctional nanoprobes (Fe3 O4 @RuSiO2 ) combing the magnetic feature of Fe3 O4 and electrochemiluminescence (ECL) performance from Ru(bpy)3 2+ @SiO2 were prepared via a facile procedure for the construction of label‐free sensing platform for the determination of marker of acute myocardial infarction‐cardiac troponin I. With our well‐structured thin layer ECL flow detection cell, the incubated hybrids can be collected on the working surface easily and detected in the presence of co‐reactants with high ECL efficiency. Integrated with the on‐line flow cleaning process and immobilization from external magnetic field, the constructed immunosensor exhibited good stability and high selectivity with the detection limit of 15.4 pg mL −1 . And the practical application was verified using human serum samples. The proposed sensor alleviated the introduction of the secondary antibody and save the time and cost, which shows great potential in the future. Abstract : Label‐free immunosensor : Bifunctional nanoprobes combining the magnetic properties of Fe3 O4 and the electrochemiluminescence (ECL) properties of Ru(bpy)3 2+ was prepared. Using our well‐structured thin‐layer ECL flow detection cell, the rapid detection of cTnI is realized via the label‐free strategy.